The Effect Of Financial Knowledge, Financial Attitude And Lifestyle On Financial Behavior On Shopee Users - Jayanti Tri Handayani; Anita Handayani (Universitas Muhammadiyah Gresik, 2022)
This study aims to test the effect of financial knowledge, financial attitudes, and lifestyle on financial behavior in management students using Shopee. The development of technology today facilitates all human affairs, including buying and selling which is increasingly facilitated. In the current condition, namely the Covid-19 pandemic, it is also able to encourage people to shop more online. The use of marketplaces among students at the University of Muhammadiyah Gresik has led to the pattern of forming student financial behavior to become more consumptive. The number of samples used in this study were 100 respondents. The analytical technique to test the hypothesis is using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that financial knowledge has a significant effect on financial behavior, financial attitudes have no significant effect on financial behavior, and lifestyle has a significant effect on financial behavior.